2019
DOI: 10.2147/jbm.s205708
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of the quality of stored blood for transfusion at Mbarara Regional Referral Hospital, Southwestern Uganda</p>

Abstract: Aim and objective: To assess the quality of blood stored for transfusion at Mbarara Regional Referral Hospital (MRRH) regarding bacterial contamination, malaria infection, and laboratory audit status. Materials and methods: Whole blood and packed red blood cells at MRRH were critically inspected for visual anomalies, and a portion of this blood was aseptically collected and analyzed for Plasmodium species and bacterial contamination using culture method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Coagulase-negative staphylococcus, Escherichia coli, which is closely related to this present finding. Rukundo et al [19], also a reported higher prevalence of Staphylococcus aureus (66.7%) of blood for transfusion at Mbarara Regional Referral Hospital, Southwestern Uganda. In a study done by Boye et al [20], also reported the highest total number of blood samples contaminated by Gram-negative and Gram-positive bacteria, atpoint-of transfusion blood in a tertiary hospital in Ghana, this agreed with the present study.…”
Section: Wondimu Et Almentioning
confidence: 90%
See 1 more Smart Citation
“…Coagulase-negative staphylococcus, Escherichia coli, which is closely related to this present finding. Rukundo et al [19], also a reported higher prevalence of Staphylococcus aureus (66.7%) of blood for transfusion at Mbarara Regional Referral Hospital, Southwestern Uganda. In a study done by Boye et al [20], also reported the highest total number of blood samples contaminated by Gram-negative and Gram-positive bacteria, atpoint-of transfusion blood in a tertiary hospital in Ghana, this agreed with the present study.…”
Section: Wondimu Et Almentioning
confidence: 90%
“…However, Tsegaye et al [12], reported a 4.5% prevalence of bacterial blood contamination at the Armed Forces Comprehensive Specialized Hospital, in Addis Ababa, Ethiopia. Rukundo et al [19], reported a 3% prevalence of bacterial contamination of blood for transfusion at Mbarara Regional Referral Hospital, Southwestern Uganda. In Nigeria Bolarinwa et al [9], reported an 8.8% prevalence of bacterial blood contamination from Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria.…”
Section: Wondimu Et Almentioning
confidence: 99%